Adaptive Fuzzy Logic Proportional-Integral-Derivative Control for a Miniature Autofocus Voice Coil Motor Actuator With Retaining Force - Yu, Hsing-Cheng; Chen, Tsan-Chen; Liu, Chien-Sheng (IEEE transactions on magnetics, 2014)
This paper presents a miniature autofocus (AF) voice coil motor (VCM) actuator with retaining force in a restricted space that can be applied in an optical AF apparatus. A position encoder consisting of a permanent magnet (PM) and a Hall-effect sensor is used to detect magnetic signals; the displacement of the AF VCM actuator can be obtained from the encoder, thus enabling closed-loop control. The proposed miniature AF VCM actuator consists of a high-permeability magnetoconductive plate and a PM on another side to generate a retaining force when the exciting current is switched off. Using a 3-D finite-element analysis simulation and the Maxwell stress tensor method, the electromagnetic Lorentz force within a movable displacement was determined to be ~16 mN. Blur caused by variable force and load disturbance was observed in images captured during AF operation. This adaptive fuzzy proportional-integral-derivative (PID) control approach compensates for the nonuniform friction, disturbance variation, and even load changes of the movable part of the AF VCM actuator that occur when a subject is photographed in various positions. The adaption mechanism reduced control effort, despite the variable force and load disturbance, and exhibited fast dynamic performance and minimal steady-state error.